P4_3 A Ring of Power - Morris, Owen William; Banks, Lewis Jefferey; Laird, Aaron James; Morris, Liam Stuart (Physics Special Topics, 2021)
Within this paper, we aim to model and calculate the maximum power produced by a circular platform around the Earth that is supporting several wind turbines. The power output of the construct is described as a function of altitude. It’s discovered that the maximum power that can be generated is approximately 0.14 GW.